2006
DOI: 10.1111/j.1399-5618.2006.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Duplication 8q22.1‐q24.1 associated with bipolar disorder and speech delay

Abstract: This finding of an unbalanced translocation provides further evidence to support previous linkage studies of a potential causative gene on 8q for bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…This feature labels the co-occurrence between psychiatric symptoms and rheumatic condition sustained by a genetic disorder. It is also noteworthy that the psychiatric profile of all members of our family largely coincides with that of Macayran et al's patients [ 12 ], who had a larger duplication than patients with definite LP with muscular-skeletal manifestations only. Moreover, the 14-year-old boy reported by Tarsitano showed a more complex phenotype, but he presented both 142 Kb duplication in 8q22.1 and 252 Kb duplication in 22q11.2.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This feature labels the co-occurrence between psychiatric symptoms and rheumatic condition sustained by a genetic disorder. It is also noteworthy that the psychiatric profile of all members of our family largely coincides with that of Macayran et al's patients [ 12 ], who had a larger duplication than patients with definite LP with muscular-skeletal manifestations only. Moreover, the 14-year-old boy reported by Tarsitano showed a more complex phenotype, but he presented both 142 Kb duplication in 8q22.1 and 252 Kb duplication in 22q11.2.…”
Section: Discussionsupporting
confidence: 80%
“…Most of the authors reported LP cases focusing their attention only on the somatic features (e.g., facial dimorphic features and skeletal and joins malformations). To the best of our knowledge, the only detailed description of psychiatric symptoms in LP was provided by Macayran et al [ 12 ]. They presented a 7-year-old boy affected by LP and bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…These results were included in a meta-analysis of 11 studies by McQueen et al (9) which reported a genome-wide significant LOD score of 3.40 in a region on chromosome 8q24 under a broad model of BP [bipolar I disorder (BP-I) and bipolar II disorder (BP-II)]. Moreover, Macayran et al (14) reported a child with BP carrying a duplication of 8q22.1-q24.1 caused by an unbalanced translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Macayran et al. (14) reported a child with BP carrying a duplication of 8q22.1‐q24.1 caused by an unbalanced translocation.…”
mentioning
confidence: 99%
“…Using methods agnostic to gene function, we have specifically implicated NOV / CCN3 , encoding a biologically-relevant protein: a) its overexpression is associated with abnormal maternal behaviour which can be reversed through antipsychotic administration (present study), b) it is located ∼138 cM on human chromosome 8, below the linkage peak indicated from a sample of individuals with bipolar affective puerperal psychosis (137.5–147.5 cM) (Jones et al, 2007), c) the associated protein is thought to modulate intracellular calcium signalling (Lombet et al, 2003) a process that goes awry in both bipolar disorder (Harrison, 2016) and PP (Riley and Watt, 1985), d) its expression is repressed by oestrogen (Vendrell et al, 2004), e) it encodes a regulator of placental angiogenesis and its expression is perturbed in cases of pre-eclampsia (Winterhager and Gellhaus, 2014), f) it is highly expressed in the cortex and limbic system of the adult human brain (Malik et al, 2015), g) it can regulate axonal outgrowth of callosal projection neurons (Park et al, 2015) consistent with corpus callosum abnormalities in PP cases (Udaya et al, 2015), h) it lies adjacent to a polymorphism associated with smoking cessation (Argos et al, 2014) and its expression is downregulated in female tissues exposed to cigarette smoke (Gueugnon et al, 2016), and i) small genomic duplications encompassing NOV / CCN3 have been associated with bipolar disorder (Macayran et al, 2006). Given possible thyroid dysfunction in PP (Bergink et al, 2011), it is also interesting that cortical Nov / Ccn3 and Adcy8 expression is regulated by 3,5,3′-triiodo- l -thyronine (T3) (Berbel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%